Kelemahan Fatwa dan Implementasinya Dalam Pengembangan Ekonomi dan Keuangan Kontemporer - Ian Rakhmawan Suherli; Iu Rusliana; Pandu Pribadi (TAFAQQUH, 2022)
This study aims to present the position, forms, factors of change, fundamental principles of establishment, and application of fatwas as references for positive law in the context of contemporary Islamic finance and economics in Indonesia. Using a literature review method, the researcher collects and analyzes literature from various primary and secondary sources, including the Qur'an, Hadith, and contemporary scholars' fatwas. The results show that fatwas, which essentially provide answers to questions of Sharia law, come in various forms and can change in response to changes in place, time, situation, tradition, knowledge, human needs, human competence, social conditions, economy, politics, and disasters. This study also highlights the importance of fundamental principles in fatwa establishment and the role of fatwas in the development of Islamic finance and economics in Indonesia, where fatwas from the DSN-MUI are often used as references in Sharia banking regulations. The contribution of this research is to provide a deep understanding of the dynamics of fatwas in contemporary Islamic economics and their role in the legal system in Indonesia